INFLUENCE OF GERMINATED RED – GRAINS SORGHUM ON PRODUCTION OF BROILER CHICKEN PERFORMANCE - N. S. Al – Rubaie; H. A . Al – Mashhadani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This experiment was conducted at the poultry Animal Production Department - College of Agricultural Engineering Sciences - University of Baghdad, for the period from 22/11/2020 to 2/1/2021 . To study the effect of adding germinated red grains sorghum (GRGS) and raw red grains sorghum(RRGS) as a complete substitute for maize to broiler diets on production performance. 225 broiler chicks were used in this experiment and randomly distributed to five treatments by 45 chicks/treatment with three replicates/treatment , 15 chicks/replicate : T1 control treatment (maize) , T2 (20%) GRGS + (80%) RRGS , T3 (40%) GRGS + (60%) RRGS , T4 (60%) GRGS + (40%) RRGS , T5 (80%) GRGS + (20%) RRGS . the data was analyzed statistically according to complete randomize design (CRD) , register Qualities understudy over three periods 1 to 10 days a starter diet, and during the period from 11 to 24 days on a growth diet, and during the period from 25 to 42 days on a finisher diet according to the production guide of Ross 308. The results were showed significant superiority (P<0.01) of the T2 treatment as compared with other treatments for the body weight and weight gain and feed intake, a significant superiority (P<0.01) in the feed conversion ratio of the T1 treatment as compared with other treatments T2, T3, T5.